(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
Wheat blast, caused by the fungus Magnaporthe oryzae pathotype Triticum (MoT), constitutes one of the major obstacles to the expansion of wheat production in Bangladesh. In the absence of resistant variety, fungicide control is the first-hand effort. Determining an effective and economic fungicide spray schedule in controlling blast disease of wheat was aimed. Ten fungicides were tested during two consecutive cropping seasons of 2018-2019 to 2019-2020. The wheat plants of blast susceptible cultivar BARI Gom 26 were inoculated with spores (107 spores ml-1) of MoT at pre-heading stage of wheat (52 days age). Fungicides were applied both before inoculation and after the appearance of blast symptoms in cocktail for three times starting from booting of wheat at 7 days interval. Plants received the combination of Filia (Tricyclazole 40% + Propiconazole 12.5%) and Seltima (Pyraclostrobin 10%) had significantly lower blast incidence and severity (1.23% and 3.33%) against untreated plants. Cocktail of Nativo and Trooper (Tricyclazole 75 wp) proved 2nd best curative measure. Application of Nativo (Tebuconazole 50% + Trifloxystrobin 25%) alone ranked third in its efficacy. The fungicide spray schedule covered booting, pre-heading and heading stages of wheat. The results indicate a mixture of Tebuconazole + Tricyclazole + Pyraclostrobin is more effective (97% blast reduction) and economic (BCR 1.45) than a single compound application in reducing incidence and severity of wheat blast. Int. J. Agril. Res. Innov. Tech. 11(1): 10-16, June 2021